Reelin Signaling Inactivates Cofilin to Stabilize the Cytoskeleton of Migrating Cortical Neurons - Frotscher, Michael; Zhao, Shanting; Wang, Shaobo; Chai, Xuejun (Frontiers in Cellular Neuroscience, 2017)
Neurons are highly polarized cells. They give rise to several dendrites but only one axon. In addition, many neurons show a preferred orientation. For example, pyramidal neurons of the cerebral cortex extend their apical dendrites toward the cortical surface while their axons run in opposite direction toward the white matter. This characteristic orientation reflects the migratory trajectory of a pyramidal cell during cortical development: The leading process (the future apical dendrite) extends toward the marginal zone and the trailing process (the future axon) toward the intermediate zone while the cells migrate radially to reach their destination in the cortical plate. In this review, we summarize the function of Reelin, an extracellular matrix protein synthesized by Cajal-Retzius cells in the marginal zone, in the development of the characteristic orientation of the leading processes running perpendicular to the cortical surface. Reelin promotes migration toward the cortical surface since late-generated cortical neurons in the reeler mutant are unable to reach upper cortical layers. Likewise, Reelin is important for the orientation and maintenance of the leading processes of migrating neurons since they are misoriented in the developing reeler cortex, as are the apical dendrites of pyramidal cells in the mature mutant. Reelin-induced phosphorylation of cofilin, an actin-associated protein, is crucial since pyramidal neurons transfected by in utero electroporation with a non-phosphorylatable form of cofilin (cofilinS3A) show severe migration defects reminiscent of those in the reeler mutant. Remarkably, migration of neurons in the cortex of reeler mice was partially rescued by transfecting them with LIM kinase 1 (LIMK1), the kinase that induces phosphorylation of cofilin at serine3, or with a pseudo-phosphorylated cofilin mutant (cofilinS3E). Together these results indicate that Reelin-induced phosphorylation of cofilin is an important component in the orientation and directed migration of cortical neurons and in their correct lamination.